New Species and New Records of Strumigenys Smith, 1860 (Formicidae: Myrmicinae) from the Neotropical schulzi Species Group - Esperidião Alves dos Santos-Neto; Júlio Cezar Mário Chaul; Jacques Hubert Charles Delabie (Taxonomy)
The genus Strumigenys is the third most diverse among ants, having been reviewed globally. Despite this comprehensive review, new species are frequently discovered in most biogeographic regions. Here, we describe two new species, Strumigenys itannae sp. nov. and Strumigenys xoko sp. nov., based on material collected in the Amazon and the Brazilian Atlantic Forest. Additionally, new records for S. castanea, S. metrix, and S. orchibia are provided, expanding the known distribution of these species. We discuss morphological variation in S. schulzi and provide biological notes that indicate some species within the schulzi group are arboreal inhabitants. We provided an identification key for the newly described species as an amendment to the identification key for the Neotropical Strumigenys.